Pengaruh Sertifikasi Halal dan Halal Awareness terhadap Minat Beli Konsumen pada Restoran All You Can Eat di Kota Surabaya - Choirul Rozi (Jurnal Syntax Admiration, 2025)
The purpose of this study was to determine the results of the analysis of the effect of halal certification on consumer purchase interest at All You Can Eat Restaurants in Surabaya City and the effect of halal awareness on consumer purchase interest at All You Can Eat Restaurants in Surabaya City. The method in this study uses a quantitative method with an associative approach, primary data sources through the distribution of questionnaires using gform. The sampling technique used in this study, the purposive non-probability technique, with a total of 104 respondents and analyzed using SmartPLS 4.0. The results showed that halal certification had a significant effect on consumer purchase interest and halal awareness also had a significant effect on consumer purchase interest.